2018
DOI: 10.1111/cge.13459
|View full text |Cite
|
Sign up to set email alerts
|

A 46,XX testicular disorder of sex development caused by a Wilms' tumour Factor‐1 (WT1) pathogenic variant

Abstract: Molecular diagnosis is rarely established in 46,XX testicular (T) disorder of sex development (DSD) individuals with atypical genitalia. The Wilms' tumour factor‐1 (WT1) gene is involved in early gonadal development in both sexes. Classically, WT1 deleterious variants are associated with 46,XY disorders of sex development (DSD) because of gonadal dysgenesis. We report a novel frameshift WT1 variant identified in an SRY‐negative 46,XX testicular DSD girl born with atypical genitalia. Target massively parallel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Structural protein remodeling suggests an increased activation of target genes, mainly NR5A1. However, these assumptions remain to be experimentally validated [70].…”
Section: Nr5a1 (Sf1) and Wt1: Old Genes New Mechanismsmentioning
confidence: 99%
“…Structural protein remodeling suggests an increased activation of target genes, mainly NR5A1. However, these assumptions remain to be experimentally validated [70].…”
Section: Nr5a1 (Sf1) and Wt1: Old Genes New Mechanismsmentioning
confidence: 99%
“…Furthermore, great interest has been paid in methods for predicting protein pathogenicity and structure based on amino acid sequence, which have become more accessible through advancements in bioinformatics tools (Touma et al, ). Pathogenic and structural analysis of rare mutations can be predicted using various computational methods (Gomes et al, ). For an accurate diagnosis of a rare mutation, it is essential to know how the mutation may affect the function of the gene to result in pathogenic effects through a combination of sequence and structure‐based algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…The variant was located in the highly conserved fourth zinc finger DNA‐binding domain of WT1 required for testis formation (Eozenou et al, 2020) (Table 4). Similarly, Gomes et al (2019) reported a patient with 46,XX testicular DSD who had a novel heterozygous p.Arg485Glyfs*14 pathogenic variant of WT1 , located in the fourth zinc finger of the protein. WT1 (OMIM # 194070) encodes a zinc finger DNA‐binding protein that has a role in transcriptional activation or repression depending on chromosomal context.…”
Section: Discussionmentioning
confidence: 90%